Development of national energy internet:index system and future trend - Chongqing KANG; Yi WANG; Jing ZHANG; Yongzhen WANG; Feng GAO; Yi LIU (Dianxin kexue)
The energy internet is the fulcrum of the new energy revolution,which will vigorously promote the high-quality and sustainable development of China’s energy industry.In order to comprehensively analyze the development of energy internet of China from the national level,the development background of energy internet was firstly reviewed,and then the connotation and extension was analyzed.On this basis,the index system of energy internet development was constructed from six aspects:policy,industry,technology,innovation,construction and public ecology.By means of literature search and analysis,official website crawler and authoritative document search,the basic status of energy internet development in China was analyzed.It was pointed out that under the multi-sectoral and multi-level policy guarantee,energy internet of China has shown a good development trend as a whole,with the healthy and prosperous development of industry,construction,technology and innovation.